Evaluating and Ranking Metaverse Platforms Using Intuitionistic Trapezoidal Fuzzy VIKOR MCDM: Incorporating Score and Accuracy Functions for Comprehensive Assessment - Isabels, Ruth; Vinodhini, Arul Freeda; Viswanathan, Anandan (Decision Making: Applications in Management and Engineering, 2024)
The purpose of this study is to develop a new approach for decision-making for addressing multi-attribute decision-making problems within a trapezoidal intuitionistic fuzzy environment, while taking into account decision makers’ psychological behavior. As a starting point, we propose and apply a distance metric model for trapezoidal intuitionistic fuzzy numbers. Then, by incorporating the expected value, score function, and accuracy value, we create a novel approach by comparing it with the results obtained from the VIKOR multi-criteria decision-making technique, allowing us to account for decision makers’ risk tolerance. Through correlation analysis, we assess the similarities and deviations in the resulting rankings. Finally, we illustrate the practical utility and feasibility of our proposed approach by evaluating the digital marketing capabilities of a few metaverse platforms using standards set in line with marketing mix criteria.